Gain-of-function EGLN1 prolyl hydroxylase (PHD2 D4E:C127S) in combination with EPAS1 (HIF-2α) polymorphism lowers hemoglobin concentration in Tibetan highlanders - Tashi, Tsewang; Scott Reading, N; Wuren, Tanna; Zhang, Xu; Moore, Lorna G; Hu, Hao; Tang, Feng; Shestakova, Anna; Lorenzo, Felipe; Burjanivova, Tatiana; Koul, Parvaiz; Guchhait, Prasenjit; et al. (Journal of molecular medicine (Berlin, Germany), 2017)
UNLABELLED: Tibetans have lived at high altitude for generations and are thought to be genetically adapted to hypoxic environments. Most are protected from hypoxia-induced polycythemia, and a haplotype of EPAS1, encoding hypoxia-inducible factor (HIF-2α), has been associated with lower hemoglobin levels. We earlier reported a Tibetan-specific EGLN1 haplotype encoding PHD2 which abrogates HIF augmentation in hypoxia. We genotyped 347 Tibetan individuals from varying altitudes for both the Tibetan-specific EGLN1 haplotype and 10 candidate SNPs in the EPAS1 haplotype and correlated their association with hemoglobin levels. The effect of the EGLN1 haplotype on hemoglobin exhibited age dependency at low altitude, while at higher altitudes, it showed a trend to lower hemoglobin levels in the presence of the Tibetan-selected EPAS1 rs142764723 C/C allele. The observed gene-environment and gene-gene interactions and the moderate effect of the EGLN1 and EPAS1 haplotypes on hemoglobin indicate that other modifiers exist. It remains to be determined whether a blunting of erythropoiesis or other physiological consequences of HIF downregulation are the primary drivers of these genetic adaptations among Tibetans. KEY MESSAGE: Most Tibetans are protected from polycythemia while living in high altitude. An EGLN1 co-adapted haplotype, EGLN1 c.12C>G, c.380G>C is uniquely Tibetan. The Tibetan EPAS1 haplotype has introgressed from the Denisovan genome. While EGLN1 and EPAS1 genotypes lower Hb, this study indicates additional Hb modifiers.
Keywords: Hypoxia; jednonukleotidový polymorfismus; Male; Tibet; aklimatizace; High-resolution melting assay; Haplotypes; mužské pohlaví; Gene-Environment Interaction; Adult; Hemoglobins; Hypoxia-Inducible Factor-Proline Dioxygenases; prolyl-4-hydroxylasy HIF; Acclimatization; transkripční faktory bHLH; Erythropoietin; Asian People; Genetic adaptation; erythropoetin; ženské pohlaví; Humans; Altitude; Basic Helix-Loop-Helix Transcription Factors; haplotypy; hemoglobiny; High altitude; nadmořská výška; dospělí; interakce genů a prostředí; Polycythemia; ferritiny; Female; Asijci; lidé; Ferritins; Polymorphism, Single Nucleotide